Extension of the results of the water quality laboratory test in the lake, Wanar Village, Pucuk District, Lamongan Regency - Eko Sulistiono; Rizki Rahadian W; Gading Wilda Aniriani; Denaya Andrya P; Mia Tri Megasari (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Water is a natural material needed for human, animal and plant life, namely as a medium for transporting food substances, as well as a source of energy and various other purposes. Water quality is one of the most important things in the superiority of plants in Wanar Village. Laboratory tests are used in this study because to determine the results of water quality in Wanar Village, Pucuk District, Lamongan Regency. The results of the laboratory test of the water of the Wanar village lake show that the physical parameters including temperature and turbidity have met the water quality standard requirements, while the TDS does not meet the water quality standard requirements. Chemical parameters including pH and nitrate met the water quality standards, while iron, COD and BOD did not meet the water quality standards. Bacteriological parameters including coliform and E.coli did not meet water quality standards. So it can be concluded that the laboratory test results show that the water of the lake in Wanar village is feasible as a means of irrigation, but the lake water is not suitable for consumption by the residents of Wanar village and its surroundings.